2003
DOI: 10.1002/app.12965
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, properties, and dyeing application of nonionic waterborne polyurethanes with different chain length of ethyldiamines as the chain extender

Abstract: This study deals with the synthesis of some nonionic waterborne polyurethanes (PUs), using ethyldiamines of different chain length, such as ethylenediamine (EDA) and diethyltriamine (DETA), as the chain extender in the reaction, and examines the thermal properties, mechanical properties, and dyeing properties of the PU products and their blends. As far as each PU by itself is concerned, we found that the T g of the one made with DETA is the highest, followed by that with EDA, and the one with 1,4-butanediol (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…It was found that the water absorption of PU film prepared with the L-lysine was higher than those of other films, but it showed the smallest hydrolysis weight loss among the three samples. Yen et al 7 studied the mechanical properties of several waterborne PUs prepared with different diamines or diols as chain extenders, such as EDA, diethyltriamine, and 1,4-butanediol, and found that the mechanical properties of the PUs prepared with diamine as chain extender were better than those prepared with 1,4-butanediol. Delpech and Coutinho 8 also studied the influence of various chain extenders on the properties of the waterborne PUs and found that the EDA-extended PU film exhibited better mechanical properties than the hydrazine-extended one.…”
Section: Introductionmentioning
confidence: 98%
“…It was found that the water absorption of PU film prepared with the L-lysine was higher than those of other films, but it showed the smallest hydrolysis weight loss among the three samples. Yen et al 7 studied the mechanical properties of several waterborne PUs prepared with different diamines or diols as chain extenders, such as EDA, diethyltriamine, and 1,4-butanediol, and found that the mechanical properties of the PUs prepared with diamine as chain extender were better than those prepared with 1,4-butanediol. Delpech and Coutinho 8 also studied the influence of various chain extenders on the properties of the waterborne PUs and found that the EDA-extended PU film exhibited better mechanical properties than the hydrazine-extended one.…”
Section: Introductionmentioning
confidence: 98%
“…This consequently leads to low dye uptake and unstable binding of the acid dyes to the polyurethane matrix that not only result in uneven coloration and poor color fastness, but also account for high dye discharge in effluents, thus posing serious environmental threats [15]. More importantly, because of the difficulty in efficiently dyeing ordinary polyurethane, more than one dyestuff is required to dye microfiber synthetic leather that complicates the dyeing process and compromises the color uniformity of the final products [16][17][18][19]. Thus, improving the dyeing properties of polyurethane toward acid dyes is crucial for fabricating microfiber synthetic leather with satisfactory uniformity and highly realistic appearance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found in the solvent‐based PU that the introduction of a proper amount of urea groups in a diol extender system would make a positive contribution to the mechanical properties of the resulting PU materials. The reason lies in the increased intermolecular hydrogen‐bonding interactions …”
Section: Introductionmentioning
confidence: 99%
“…The reason lies in the increased intermolecular hydrogen-bonding interactions. 12 In our previous work, 13 we reported an alkoxysilane-modified diol extender (DEA-Si) in which the trimethoxysilane group was connected to the diethanolamine structure by an alkyl-ester segment. Here, in order to further improve the aggregating strength of WPU film, we substituted the ester linkage with the urea linkage and synthesized a new diol-bearing pendant ureapropyl trimethoxysilane (APD-Si).…”
Section: Introductionmentioning
confidence: 99%